Characterization of Alumina and H-ZSM-5 Zeolite and Comparison of their Performance by Toluene Methylation Reaction with Ceramic Foam as Catalyst Support - Ghosal, Debarpita; Sengupta, Sonali; Kumar Basu, Jayanta (Current Catalysis, 2015)
The present work deals with the characterization and comparison of ceramic foam (dimension 40×40×15mm, 30 pores per inch) supported mesoporous alumina(prepared by the surface hydrolysis of 99% Al metal plate as well as by hydrothermal synthesis of Al(NO3)3.9H2O using pluronic F-127 as structure directing agent), and H-ZSM-5 for the methylation of toluene reaction. The characterization of the catalyst was done by XRD, SEM, Particle size distribution, Ammonia TPD, BET surface area, and pore size distribution. It was observed that alumina prepared with pluronic F-127 shows higher BET surface area (320 m2/g) compared to commercial H-ZSM-5(260 m2/g). Toluene alkylation reaction with methanol was carried out with catalyst coated foam and also with catalyst extrudates (both1g). Conversion obtained was 25-30% at a catalyst loading of 8% on foam for H-ZSM-5 whereas it was 1.26% for alumina coated one. It can also be concluded that catalyst coated ceramic foam exhibits higher conversion compared to pelleted one due to less mass transfer resistance and uniform distribution of catalyst active sites. For any chosen reaction like alkylation, the greater surface area for any catalyst is not the only reason for higher conversion, but the bronsted and lewis acid sites play an important role.
Keywords: toluene methylation